Protective Role of Vitamin B1 in Doxorubicin-Induced Cardiotoxicity in Rats: Focus on Hemodynamic, Redox, and Apoptotic Markers in Heart - Rankovic, Marina; Draginic, Nevena; Jeremic, Jovana; Samanovic, Andjela Milojevic; Stojkov, Svetlana; Mitrovic, Slobodanka; Jeremic, Nevena; Radonjic, Tanja; Srejovic, Ivan; Bolevich, Sergey; Svistunov, Andrey; Jakovljevic, Vladimir; et al. (Frontiers in Physiology, 2021)
Up until now, the specific mechanisms involved in doxorubicin (DOX)-induced cardiotoxicity have not been fully elucidated. Since thiamine deficiency is associated with myocardial dysfunction and it may lead to cardiomyopathy, we aimed to investigate whether thiamine (Vitamin B1) treatment provides cardioprotection and modulates DOX mediated subchronic cardiotoxicity as well as to determine possible mechanisms of its effects. The study involved 48 Wistar albino rats divided into four groups: healthy non-treated rats and healthy rats treated with thiamine and DOX rats without treatment and DOX rats treated with thiamine. DOX was applied as a single i.p.injection (15mg/kg), while thiamine treatment lasted 7days (25mg/kg/dayi.p.). Before and after the treatment hemodynamic changes were monitored in vivo by echocardiography. When the protocol was completed, animals were sacrificed and rat hearts were isolated in order to evaluate parameters of cardiac oxidative stress [superoxide anion radical-O2−, hydrogen peroxide-H2O2, nitric oxide-NO−, index of lipid peroxidation-thiobarbituric acid (TBA) reactive substances (TBARS), superoxide dismutase – SOD, catalase (CAT), and reduced glutathione-GSH] and apoptosis (Bax, Bcl-2, caspases). DOX treatment significantly reduced the ejection fraction, while thiamine treatment led to its minor increase in the DOX-treated group. In that sense, heart oxidative stress markers were significantly increased in DOX-treated rats, while therapeutic dose of thiamine decreased the levels of free radicals. Our study demonstrated the promising ameliorative effects of thiamine against DOX-induced cardiotoxicity through modulation of oxidative stress, suppression of apoptosis, and possibility to improve myocardial performance and morphometric structure of rats` hearts.